Effect of the res2 transcription factor gene deletion on protein secretion and stress response in the hyperproducer strain Trichoderma reesei Rut-C30 - Jawad Alharake; Frédérique Bidard; Thiziri Aouam; Catherine Sénamaud-Beaufort; Antoine Margeot; Senta Heiss-Blanquet (BMC Microbiology, 2023)
Abstract Background The fungus Trichoderma reesei is one of the most used industrial cellulase producers due to its high capacity of protein secretion. Strains of T. reesei with enhanced protein secretion capacity, such as Rut-C30, have been obtained after several rounds of random mutagenesis. The strain was shown to possess an expanded endoplasmic reticulum, but the genetic factors responsible for this phenotype remain still unidentified. Recently, three new transcription factors were described in Neurospora crassa which were demonstrated to be involved in protein secretion. One of them, RES2, was involved in upregulation of secretion-related genes. The aim of our present study was therefore to analyze the role of RES2, on protein secretion in the T. reesei Rut-C30 strain. Result Deletion of the res2 gene in Rut-C30 resulted in slightly slower growth on all substrates tested, and lower germination rate as well as lower protein secretion compared to the parental strain Rut-C30. Transcriptomic analysis of the Rut-C30 and the Δres2 mutant strain in secretion stress conditions showed remarkably few differences : 971 genes were differentially expressed (DE) in both strains while 192 genes out of 1163 (~ 16.5%) were DE in Rut-C30 only and 693 out of 1664 genes (~ 41.6%) displayed differential expression solely in Δres2. Notably, induction of protein secretion by cultivating on lactose and addition of secretion stress inducer DTT induced many genes of the secretion pathway similarly in both strains. Among the differentially expressed genes, those coding for amino acid biosynthesis genes, transporters and genes involved in lipid metabolism were found to be enriched specifically in the Δres2 strain upon exposure to lactose or DTT. Besides, redox homeostasis and DNA repair genes were specifically upregulated in the Δres2 strain, indicating an altered stress response. Conclusion These results indicate that in the T. reesei Rut-C30 strain, RES2 does not act as a master regulator of the secretion pathway, but it contributes to a higher protein secretion by adjusting the expression of genes involved in different steps of protein synthesis and the secretion pathway.